THE RURAL DEVELOPMENT POLICY OF THE EUROPEAN UNION FROM THE PERSPECTIVE OF ROMANIAS INTEREST - Stefan Bogdan, Lucov (Economics of Agriculture, 2012)
The rural development component of the Common Agricultural Policy has gained increased attention after the Commission developed the strategic document Agenda 2000, thus becoming the second pillar of the CAP. There are two major reasons for an approach in this direction: firstly, the percentage of agricultural land compared to the surface of the European Union is very high - about 90%; secondly, the primary objective of economic and social cohesion promoted by the European Union, whose achievement would be utopic without due attention to the harmonious development of rural areas. The rural development policies are designed to improve the living standards of the rural population. The development of rural economy depends both on the communities own efforts, and on the state institutions. Government intervention is required to multiply the local creative potential, not only by providing a good strategy, but also the necessary financial means. This requirement can be achieved in the context of the following four important dimensions of the policy: quality of life, creating employment opportunities, regional balance, the populations self-confidence. The Common Agricultural Policy must be maintained by adapting it to the new common goals set by the European Commission, which, in one of its versions, proposes the reduction of allocations in the form of direct aid. Financing rural development should be seen in the context of the cohesion policy, which would relieve pressure on CAP reserved expenditure. In this respect, it is recommended to rethink the allocations for Pillar 2 and to find co-financing methods for Pillar 1. In this context, Romania has to negotiate within the EU the new rural development program for the 2014-2020 period, starting from the concrete situation of Romanian villages, and taking into account the interests of residents and potential investors in rural areas.